2020
DOI: 10.1177/1066480720902410
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Cognitive Behavioral Couple Therapy on Reducing Depression and Anxiety Symptoms and Increasing Dyadic Adjustment and Marital Social Skills: An Exploratory Study

Abstract: Several kinds of marital conflict might be solved through constructive communication, development of interaction skills, and behavioral and thought modification. The aim of this study was to show results of the application of a protocol based on cognitive behavioral couple therapy (CBCT) on dyadic adjustment, marital social skills, depression, and anxiety symptoms. The sample consisted of 32 participants (16 couples) divided in two groups by length of marriage: Group 1 (1–7 years) and Group 2 (8–12 years). All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 56 publications
2
12
0
7
Order By: Relevance
“…The interpretation of BDI-II scores segments depression severity into several categories: Recent studies [36][37][38] and clinical observations highlight the need for comprehensive interventions in marital conflict, addressing both overt manifestations and underlying depression. This underscores the significance of BDI-II as a tool for assessing the severity of emotional distress and its potential ramifications on marital harmony.…”
Section: Test Administer: Bdi-ii Score Analysis Of Clientmentioning
confidence: 99%
“…The interpretation of BDI-II scores segments depression severity into several categories: Recent studies [36][37][38] and clinical observations highlight the need for comprehensive interventions in marital conflict, addressing both overt manifestations and underlying depression. This underscores the significance of BDI-II as a tool for assessing the severity of emotional distress and its potential ramifications on marital harmony.…”
Section: Test Administer: Bdi-ii Score Analysis Of Clientmentioning
confidence: 99%
“…However, the possible potential of CBT for students remains unrecognized, particularly for international students with a certain degree of anxiety and additional risk coping caused by adaptation to a new country with different academic environments and expectations. Cognitive Behavioral Couple Therapy (CBCT) techniques aim to help couples with poor communication skills and great problem-solving difficulties, affecting the interaction process in their relationship (Durães et al, 2020). According to a standardized treatment manual, treatment in CBT consists of eight individual therapy sessions, equally divided into anxiety management training and exposure therapy using a virtual audience (Anderson et al, 2005).…”
Section: The Primacy Of Cbt To Address Public Speaking Anxietymentioning
confidence: 99%
“…As such, these treatments could not be placed within the first two levels of efficacy. However, both recent case studies and pre-test post-test studies of treating anxiety within a marital or family context (e.g., Chambless, 2012;Durães et al, 2020;Robinson et al, 2011) have shown promise. This evidence would be sufficient to classify family based treatments for adult anxiety as "Level 4: Experimental Interventions" (Southam-Gerow & Prinstein, 2014).…”
Section: Evidentiary Statusmentioning
confidence: 99%